The Resilience of Microbial Community under Drying and Rewetting Cycles of Three Forest Soils - Zhou, Xue; Fornara, Dario; Ikenaga, Makoto; Akagi, Isao; Zhang, Ruifu; Jia, Zhongjun (Frontiers in Microbiology, 2016)
Forest soil ecosystems are associated with large pools and fluxes of carbon (C) and nitrogen (N), which could be strongly affected by variation in rainfall events under current climate change. Understanding how dry and wet cycles influence the metabolic state of indigenous soil microbes is crucial to predicting forest soil responses to future climate change. We used 454 pyrosequencing and quantitative PCR to explore the response pattern of present (DNA-based) and potentially active (RNA-based) soil bacterial communities to the changes in water availability in three different forest types located across two continents (Africa and Asia) under controlled drying and rewetting cycles. Sequencing of rRNA gene and transcript indicated that Proteobacteria, Actinobacteria and Acidobacteria were the most responsive phyla to changes in water availability. Here in this study, the ratio of rRNA transcript to rRNA gene abundance was defined as the indicator of potential activity of microorganisms, we found that the ratio was increased by dry-down and declined by rewetting. Following rewetting Crenarchaeota-like 16S rRNA gene transcript increased in some forest soils and was linked to increases in soil nitrate levels suggesting greater nitrification rates when soil water is available. The different response pattern of the relative abundance in phyla and class level as well as of the abundance in 16S and amoA gene were both site-specific and taxa-specific and might be driven by different life-strategies of microorganism. Overall, we found that, upon rewetting, the present and potentially active bacterial community structure as well as the abundance of bacterial (16S), archaeal (16S) and ammonia oxidizers (amoA), all returned to pre-dry-down levels, suggesting that taxa have the ability to recover from desiccation, contributes to the maintenance of microbial biodiversity in harsh ecosystems with continues environmental perturbations, such as the change of water availability.